2005
DOI: 10.1007/s00441-005-1080-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characterisation of follicle-associated epithelium of rectal lymphoid tissue

Abstract: Lymphoid follicles cluster in the terminal rectum of various animal species and of man and hence this site may be important in the development of immune responses to pathogens. For the induction of immune responses at mucosal sites, interplay is required between various cell types performing functions ranging from antigen-sampling cells via antigen-presenting cells to antigen-specific lymphocytes. Therefore, we have characterised the cell populations and relevant functioning of follicle-associated epithelium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
2
19
1
1
Order By: Relevance
“…Moreover, macrophages, with numerous intracellular beads, were seen in epithelial and submucosal regions. Similarly, a previous study of lymphoepithelium at the bovine rectoanal junction found microparticles in submucosal regions after 60 min incubation, evidence of microparticle transcytosis (Mahajan et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Moreover, macrophages, with numerous intracellular beads, were seen in epithelial and submucosal regions. Similarly, a previous study of lymphoepithelium at the bovine rectoanal junction found microparticles in submucosal regions after 60 min incubation, evidence of microparticle transcytosis (Mahajan et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
“…Microparticles were limited to apical regions of calf rectoanal lymphoepithelium at 45 min; however, after 60 min incubation, microparticles were found in submucosal regions (Mahajan et al, 2005). Ex vivo experiments to examine microparticle transcytosis in rabbit conjunctival lymphoepithelium revealed that with incubation times as short as 20 min at 37 C, a greater number of microparticles were present within the submucosa compared to epithelial regions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The terminal rectum is an area rich in lymphoid follicles (21), and it has been suggested that adherence to these sites may explain the tropism of E. coli O157:H7 bacteria for the bovine terminal rectum (25). In this study, extensive histological examination of terminal rectal tissues did not reveal a prominent association between E. coli O157:H7 microcolonies and follicle-associated epithelium.…”
contrasting
confidence: 44%
“…In cattle, the terminal rectum is rich in lymphoid FAE containing M cells (49). Since this is the predominant site colonized by EHEC O157 in cattle (60), we hypothesized that EspF may have an important role in cattle colonization by inhibiting translocation of the organism by M cells and that the sequence differences of EspF in EHEC O157:H7 may reflect selection for its function in the bovine host.…”
Section: Is Important For the Inhibition Of Phagocytosis By Epec And mentioning
confidence: 99%